Pengaruh Pelatihan Regulasi Emosi untuk Meningkatkan Subjective Well-Being pada Orangtua dengan Anak Berkebutuhan Khusus (ABK) - Nurlaela, Siti (PSIKOPEDAGOGIA Jurnal Bimbingan dan Konseling, 2016)
This study aimed to improve the subjective well-being on Parents of children with special needs through emotion regulation training. This was a quantitative study with pre-test post-test one group design. The subjects of this study were 12 Parents whose children participated in the early childhood education activities on the RW of Umbulharjo subdistrict. The data collection instruments for this study were well-being scale, observation sheet, and interview guideline. The data analysis technique of this study was Wilcoxon formula to compare the score of pre-test, post-test, and follow-up. The result of this study showed that emotion regulation training could improve subjective well-being on parents of children with special needs. This study can be a reference for the guidance and counseling implementation unit on the university, lecturers, and the counselor to improve emotion regulation for improving subjective well-being on parents of children with special needs.